2019
DOI: 10.1080/20477724.2019.1624076
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Plasmodium falciparum genetic diversity among asymptomatic and symptomatic children in three epidemiological areas in Cote d’Ivoire

Abstract: Asymptomatic carriers of Plasmodium are considered a reservoir of the parasite in humans. Therefore, in order to be effective, new malaria elimination strategies must take these targets into account. The aim of this study was to analyse genetic diversity of Plasmodium falciparum among schoolchildren in three epidemiological areas in Côte d'Ivoire. This was a crosssectional study carried out from May 2015 to April 2016 in a primary school in rural and urban areas of San Pedro, Grand-Bassam and Abengourou, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The IC/3D7 family has been associated with asymptomatic infections and is thought to protect against clinical malaria [ 16 , 37 , 38 ]. However, contradictory findings have reported that parasites carrying FC27 like alleles are more prevalent among asymptomatic carriers [ 15 , 39 ]. There is no clear consensus on whether the two msp2 allelic families are likely to be found in asymptomatic or symptomatic infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC/3D7 family has been associated with asymptomatic infections and is thought to protect against clinical malaria [ 16 , 37 , 38 ]. However, contradictory findings have reported that parasites carrying FC27 like alleles are more prevalent among asymptomatic carriers [ 15 , 39 ]. There is no clear consensus on whether the two msp2 allelic families are likely to be found in asymptomatic or symptomatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphic block 3 contains repeats that vary in number, length and sequence that are grouped into two allelic families i.e. IC/3D7 and FC27 [ 14 ] that are associated with different malaria outcomes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, much empirical research on the impacts of drought on parasite ecology has focused on disease prevalence/incidence as well as vector population size and distribution (see Gagnon, Smoyer-Tomic & Bush, 2002 ; Brown, Medlock & Murray, 2014 ), but to our knowledge, no study has reported on the effects of drought on infection complexity. While previous studies on human malaria have shown changes in COI during wet and dry seasons in Africa, these studies did not specifically measure for drought conditions (for example: Gnagne et al, 2019 ; Collins et al, 2022 ). Infection complexity, although often correlated with disease prevalence ( Wanji et al, 2012 ; Tusting et al, 2014 ; Gatei et al, 2015 ; Fola et al, 2017 ), can be high despite overall low prevalence and vice versa ( e.g ., Barry et al, 2013 ; Gunawardena et al, 2014 ; Fola et al, 2017 ; Koepfli & Mueller, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notable amongst these markers are the genes encoding surface antigens found at the developmental stages of the parasite life cycle, particularly the blood-stage antigens Merozoite surface protein 1 (MSP-1) and 2 (MSP-2), which are known to be highly polymorphic. Several studies have utilized PCR typing of the MSP-2 locus alone or together with the MSP-1 locus to assess genetic diversity and complexity of P. falciparum infections in different communities with varying transmission intensities and among infected individuals with different clinical presentations of malaria [21][22][23][24][25][26][27][28][29]. However, little is known about the diversity of P. falciparum infections at the level of the microenvironment, among members of the same household.…”
Section: Introductionmentioning
confidence: 99%